Cultural Sufism and the Formation of Santri Habitus: The Symbolic Strategies of Kiai Mutamakkin in Serat Cebolek - Abdul Rosyid; Sartini Sartini; Siti Murtiningsih (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Islamization in Java developed through the interaction between Islamic teachings, Sufism, and local culture. Studies on Kiai Mutamakkin in the Serat Cebolek have mainly seen him as a political figure, an ideal of Javanese Islam, or a symbol of moderation. However, little attention is paid to how Sufi cultural practices shape the santri habitus and produce religious authority. This article examines how the santri’s habitus forms and authority emerges through Kiai Mutamakkin’s symbolic strategies in the Serat Cebolek. The primary source is the Serat Cebolek version by Van Dorp, transliterated by Soebardi. This literature review uses documentation and analyzes data with Paul Ricoeur’s hermeneutics and Pierre Bourdieu’s theory of praxis, focusing on habitus, capital, field, and symbolic strategy. Findings show the santri’s habitus forms through cultural Sufi practices using Javanese symbols, such as the Dewa Ruci narrative and religious pedagogy. These practices help internalize religious values in a reflective, context-aware way. The study also finds that Kiai Mutamakkin uses cultural, social, and symbolic capital, converting them into religious legitimacy recognized by his community and followers. Using symbolic strategies, he links Sufism with local culture, building alternative religious authority outside formal Keraton structures. This article supports studies on Nusantara Islam and Islamic anthropology by showing that cultural Sufism shapes the santri habitus, creates legitimacy, and forms community-based authority.